A Case of Hypophysitis Associated With SARS-CoV-2 Vaccination - Ankireddypalli, Anvitha R.; Chow, Lisa S.; Radulescu, Angela; Kawakami, Yasuhiko; Araki, Takako (AACE clinical case reports, 2022)
Although SARS-CoV-2 vaccines have been developed with multiple novel technologies and rapidly disseminated worldwide, the full profile of adverse effects has not been known. Recently, there are sporadic but increasing reports of endocrinopathy in relation to SARS-CoV-2 vaccination. Here we report a rare case of hypophysitis with acute onset of diabetes insipidus, immediately after SARS-CoV-2 vaccination. A 48-year-old female patient had been in her usual state of health until she received the first SARS-CoV-2 vaccine. Two days after vaccination, she started to have flu-like symptoms, including severe headache and myalgia as well as persistent headache, polydipsia, and polyuria. She was diagnosed with diabetes insipidus, and magnetic resonance imaging revealed thickening of the pituitary stalk. Three months after vaccination, her symptoms had somewhat improved, but she still had pituitary stalk thickening on magnetic resonance imaging. Given the timing of the occurrence of diabetes insipidus, we believe that the patient’s hypophysitis may be associated with SARS-CoV-2 vaccination. We also found 19 cases of endocrinopathy after SARS-CoV-2 vaccination by literature search. The reported endocrine organs were the thyroid, pituitary, and adrenals. Twelve cases of diabetes were also reported. Among 3 pituitary cases, diabetes insipidus was reported only in our case. We report a rare case of SARS-CoV-2 vaccine-triggered hypophysitis, which led to diabetes insipidus. SARS-CoV-2 vaccine–related endocrinopathy seems, indeed, possible. Endocrinopathy is associated with infrequent complications; however, it may be underestimated in the post–SARS-CoV-2-vaccinated population. Further studies are warranted to better understand SARS-CoV-2 vaccine–related endocrinopathy.